Basic Tips for Designing Efficient Irrigation Systems - Haimanote K. Bayabil; Kati W. Migliaccio; Michael D. Dukes; Laura Vasquez (EDIS, 2020)
As freshwater resources become increasingly scarce and droughts become more frequent, there is a need for efficient use of water resources. Designing efficient irrigation systems and equipment will not only save money but also conserve water. This 10-page fact sheet discusses factors to consider when designing irrigation systems. Written by Haimanote K. Bayabil, Kati W. Migliaccio, Michael Dukes, and Laura Vasquez, and published by the UF/IFAS Department of Agricultural and Biological Engineering, February 2020. https://edis.ifas.ufl.edu/ae539